Responses of Al-Zamlkani Died in 651 Hijri in his book " Ghayat Al muhassal fi sharh Al mofassal" to Al-Zamakhshari and Abn-Al Hajeb in the names section: presentation and study - Al-Wargash, Wadha Ahmad Mossad (Arab Journal for Sciences and Research Publishing, 2021)
This research aimed to identify some of Al-Zamlkani's responses and evaluate them according to the experts of linguistics using the descriptive and analytical method. This was achieved with a presentation of a brief translation of Al-Zamlkani; as the research centered on collecting the scholar's responses in his explanation in the nouns' chapters and his genres and grammatical aspects in more than one chapter. This includes a response to an Absolute Had (limit) that needed a restriction, or certain expressions that confuse the scholar; thus, where incorrectly studied. As for his response to Ibn al-Hajib in the chapter related to his personal perspectives presented in this explanation, he opposed him on the one aspect; while defended what Al-Zamakhshari mentioned about some of them in other chapters.These issues were presented in two topics: The first was Al-Zamlkani's responses to Al-Zamakhshari and Ibn al-Hajib in the nouns' categories; while the second was Al-Zamlkani's responses to al-Zamakhshari and Ibn al-Hajib in the aspects of noun parsing.The most important results demonstrated by the research were that Al-Zamlkani was seeking to facilitate the language and clarify the grammatical issues; as his responses varied when discussing Al-Zamakhshari; including a response to an Absolute Had that required restriction or expressions that confuse the scholar; thus, where incorrectly studied. Al-Zamlkani also dealt with chapters of certain grammatical aspects; where his responses showed reliance on the logical aspect and philosophical thought at times and on his sheik and teacher Ibn al-Hajib’s belief at other times by quoting what was explicitly or implicitly mentioned. The lack of interpretation and clarification in some of Al-Zamakhshari's phrases is a reason for the confusion that does not have a meaning for the scholars, including Al-Zamlkani.
Keywords: Arabic Grammar; Al-Zamalkani; Al-Zamakhshari; The book (Ghayat al-Muhassal fi Sharh al-Mufassal)